An investigation of skeletons from Type-R settlements along the Riet and Orange Rivers, South Africa, using stable isotope analysis - Masemula, Nandi (Department of Archaeology, 2015)
In the last centuries before incorporation into the Cape Colony, the Riet and Orange River areas of the Northern Cape, South Africa were inhabited by communities of hunter-gatherers and herders whose life ways are little understood. These people were primarily of Khoesan descent, but their large stone-built stock pens attest to the presence of substantial herds of livestock, very likely for trade. This region was too dry for agriculture, although we know that there were links with Tswana-speaking agricultural communities to the north, because of the presence of characteristic styles of copper artefacts in Riet River graves. This was a frontier region at a turbulent time in South African history, so one of the questions about these societies is the extent to which they were homogeneous or heterogeneous - were many outsiders incorporated into these communities? What was the relative importance of herding compared with hunting in the local economy? Did connections with farming communities extend to the trading of cereal foods?